Combination of Fresh Frozen Plasma and Cryosupernatant Plasma for Therapeutic Plasma Exchange in Thrombotic Thrombocytopenic Purpura: A Single Institution Experience. (30th January 2019) - Lin, Qiuyan; Fan, Liping; Huang, Haobo; Zeng, Feng; Fu, Danhui; Wei, Shijin
Abstract : Purpose . To evaluate the impact of a combination of fresh frozen plasma (FFP) and cryosupernatant plasma (CP) as a replacement fluid in therapeutic plasma exchange (TPE) on early therapeutic response and long-term survival of patients with thrombotic thrombocytopenic purpura (TTP). Materials and Methods . A total of 44 patients with suspected TTP were screened by Bentley and PLASMIC scores. Twenty-seven patients treated with TPE using the FFP and CP combination as the replacement fluid were enrolled and divided into two groups: 11 patients who received TPE with CP-dominant replacement fluid (FFP/CP<1) and 16 patients who received TPE with FFP-dominant replacement fluid (FFP/CP>1). Results . There were no significant differences in the demographic and clinicopathological characteristics between the two groups except for the international normalized ratio (INR). The number of TPE procedures was lower, and time to achieve complete response was shorter in the CP-dominant group than in the FFP-dominant group. There were no significant differences in overall survival between the two groups. Conclusion . The CP-dominant replacement fluid was superior to the FFP-dominant replacement fluid in early response to TPE in patients with TTP, but did not impact the patients' overall survival.